Associations of Sun Exposure with 25-Hydroxyvitamin D and Parathyroid Hormone Levels in a Cohort of Hypertensive Patients: The Graz Endocrine Causes of Hypertension (GECOH) Study - Stefan Pilz; Katharina Kienreich; Daniel Stückler; Andreas Meinitzer; Andreas Tomaschitz (International Journal of Endocrinology)
Sunlight-induced vitamin D, synthesis in the skin is the major source of vitamin D, but data on the relationship of sun-related behaviour with vitamin D and parathyroid hormone (PTH) levels are relatively sparse. We evaluated whether habitual sun exposure is associated with 25-hydroxyvitamin D (25[OH]D) and PTH levels and whether there exist seasonal variations. We examined 111 hypertensive patients in Austria (latitude 47° N). Frequent sunbathing at home and outdoor sports were associated with higher 25(OH)D levels (P<0.05 for both). Red or blond scalp hair as a child, memory of sunburns, preferring sunbathing, frequent stays on the beach or in open-air pools, and solarium use were associated with lower PTH levels (P<0.05 for all). Multiple linear regression analyses including age, sex, and body mass index showed that sun exposure score was significantly associated with 25(OH)D (beta coefficient=0.27; P=0.004) and by trend with PTH (beta coefficient=−0.16; P=0.09). These associations were more prominent in summer in which 25(OH)D levels were significantly higher compared to winter. Translation of these findings into recommendations for the prevention and treatment of vitamin D deficiency remains a challenge for the future.